2019
DOI: 10.1038/s41524-019-0179-y
|View full text |Cite
|
Sign up to set email alerts
|

Microphase separation of a miscible binary liquid mixture under confinement at the nanoscale

Abstract: Recent experimental works suggested that the confinement into a cylindrical nanopore induced the microphase separation of a binary liquid, despite the miscible character of its bulk counterpart. A core-shell organization was evidenced such that one of the liquids was strongly anchored to the solid surface whereas the other was confined at the center of the pore. At the same time, a study based on atomistic simulations suggested a strong heterogeneity and the absence of a separation. In this work, by refining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Moreover, in the past couple of decades, confined solutions have attracted a lot of attention due to their diverse potential applications in electronics, engineering, and biomedical fields. For a confined system, fluids exhibit distinct phases and flow properties not shown in the bulk solution. For instance, it was found that the fluid flow in carbon nanotubes can be enhanced further than the predicted flow by the conventional fluid-flow theory. , This is caused by the spatial constraint and influence of solid–liquid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the past couple of decades, confined solutions have attracted a lot of attention due to their diverse potential applications in electronics, engineering, and biomedical fields. For a confined system, fluids exhibit distinct phases and flow properties not shown in the bulk solution. For instance, it was found that the fluid flow in carbon nanotubes can be enhanced further than the predicted flow by the conventional fluid-flow theory. , This is caused by the spatial constraint and influence of solid–liquid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…While they were interpreted in terms of core-shell models for confined alcohols [ 33 , 97 ], they were attributed to coexisting liquid and solid phases or high-density and low-density liquid phases for confined water [ 78 , 86 , 98 ]. In our case of binary mixtures, another possible explanation resulted from the finding that preferential interactions with the pore walls could lead to microphase separation and, thus, to bimodal dynamics [ 28 , 29 , 40 , 43 , 44 , 99 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…23 This observation was also confirmed by a molecular dynamics simulation study, which brought a deeper insight into this phenomenon at the molecular scale. 24 This direct experimental evidence of the core−shell organization represents a unique insight into allowing the investigation of the particular dynamical properties of these novel systems. Indeed, we evaluated the phase behavior and the glassy dynamics of TBA−TOL binary liquids confined in MCM-41 by the combination of neutron diffraction and differential scanning calorimetry (DSC) measurements in an attempt to examine the thermal behavior of this unusual phase in terms of density and heat capacity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The LJ parameters between the silica nanopore and the TOL molecules have been optimized 8 to qualitatively reproduce the experimental isotherms. 24 The so-optimized interactions between TOL molecules and silica material are provided in Table 1. Force field parameters of silica material, TOL, and TBA and crossed interactions are provided in the FIELD.txt file of DL_POLY software.…”
mentioning
confidence: 99%